Selection of strawberry genotypes resistant to the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) using micropropagated plants - Dávalos González, Pedro Antonio; Bujanos Muñiz, Rafael; Rodríguez Rodríguez, José Francisco; Aguilar García, Ramón; Rodríguez Guillén, Alejandro; Jofre y Garfias, Alba Estela; Marín Jarillo, Antonio (Revista Colombiana de Entomología, 2024)
The two-spotted spider mite, Tetranichus urticae (Acari: Tetranychidae) is the main strawberry pest in the states of Michoacán and Guanajuato, Mexico. Its management depends mainly on the application of synthetic acaricides, where farmers in Guanajuato make at least 10 applications of acaricide products per season. With the objectives of identifying strawberry genotypes resistant to the mite and testing an infestation technique in micropropagated plants, 48 clones were evaluated, which included foreign varieties and advanced strawberry selections from the INIFAP Product System Genetic Improvement Program. Based on an arbitrary scale from 0 to 10, where 0 was no spiders and 10 a high population, the 48 clones were classified into the following five categories. Extremely resistant: ’Florida Belle’, ’Sequoia’ ’Fairfax’, 98,32, 08,492, F. vesca clone Guanajuato and UC-4; Resistant: ’Capitola’, ’Dabreak’, ’Solana’, ’92,1E6’, ’07,168’, ’10,37’, ’99,849’, ’07,4’ and ’99,139’; Tolerant: ’San Andreas’, ’Tioga’, ’Festival’, ’Cometa’, C-15,3’, ’07,35’, ’06,76’, ’00,142’, ’10,14’, ’10,25’, ’99,185’, ’07,207 ’, ’10,40’ and ’07,90’; Susceptible: ’Aromas’, ’Albritton’, ’Camarosa’, ’Buenavista’, ’Dover’, ’08,268’, ’99,24’, ’08,453’, ’02,81’, ’08,279’ and ’07,198’; Extremely susceptible: ’Douglas’, ’Andana’, ’Seascape’, ’02,11’, ’01,150’, ’01,70’ and ’10,16’. The infestation of micropropagated plants had several advantages: avoiding the use of mite-infested vegetative material in strawberry mite susceptibility studies, allowing good colonization with induced infestation, and facilitating evaluation of a large group of genotypes in a small space over a period of time. short period of time.